Under Their Wing: A Case Study of Caring Adults Who Support Homeless Youth - Christina L Helfrick (International Journal of School Social Work, 2024)
Despite many risk factors, few interventions exist to support youth who are homeless. Theories of resilience and social capital offer support for the development of a school-appointed, homeless, student advocate program. However, these theories do not offer a process or description of activities or qualities of an advocate. This case study is used as an initial step in intervention development. A one-time, focus-group was utilized as a purposeful sample of individuals experienced with supporting homeless youth will be used to create a framework for practice. This study asked the following questions: What is a programmatic framework for a school-appointed homeless advocate program? And what are the qualities and activities of advocate for homeless youth? The findings indicate that what is most important is the qualities that the advocate possesses: who they are, rather than what they do. A framework was developed that demonstrates that the qualities of the individual are the foundation of the advocate, and these qualities cause them to activate others and complete activities focused on the youth, to increase the well-being of the homeless youth.
Keywords: Intervention research; homeless youth; McKinney-Vento; Advocate